Bartonella massiliensis sp. nov., a new bacterial species isolated from an Ornithodoros sonrai tick from Senegal - H. Medkour; C.I. Lo; H. Anani; F. Fenollar; O. Mediannikov (New Microbes and New Infections, 2019)
Bartonella massiliensis sp. nov., strain OS09T (= CSURB624T = DSM 23169), is the type strain of Bartonella massiliensis sp. nov., a new species within the genus Bartonella. It was isolated from a soft tick, Ornithodoros sonrai, vector of recurrent fever collected from Senegalese domestic rodent burrows. This strain is an aerobic, rod-shaped and Gram-negative bacterium. On the basis of taxonogenomic approach, we propose the creation of Bartonella massiliensis sp. nov. Keywords: Bartonella massiliensissp. nov., genome, Ornithodoros sonrai, senegal, soft tick